Burnett County LAKELines newsletter survey report, 2013 - Janke, James; Trechter, David (My University, 2013)
The purpose of this study was to gather recipients' opinions about the LAKELines newsletter produced by the Burnett County UW-Extension Department and Burnett County Lakes and Rivers Association.
23 p.
Keywords: Burnett County, Wisconsin; Burnett County (Wis.); Burnett County (Wis.)--Survey; Public opinion--Wisconsin--Burnett County